Insulin‐like growth factor I and risk of breast cancer by age and hormone receptor status—A prospective study within the EPIC cohort. Issue 11 (19th November 2013) - Kaaks, Rudolf; Johnson, Theron; Tikk, Kaja; Sookthai, Disorn; Tjønneland, Anne; Roswall, Nina; Overvad, Kim; Clavel‐Chapelon, Françoise; Boutron‐Ruault, Marie‐Christine; Dossus, Laure; Rinaldi, Sabina; Romieu, Isabelle; et al.
<x xml:space="preserve">Abstract</x> Experimental evidence shows cross‐talk in mammary cells between estrogen, insulin‐like growth factor I (IGF‐I) and their respective receptors and possible synergistic effects of estrogen receptor (ER) activation and increased IGF‐I signaling with regard to breast tumor development, and epidemiological evidence suggests that circulating IGF‐I levels may be related more to the risk of ER‐positive than ER‐negative breast cancer. Using a case–control study nested within the prospective European EPIC cohort (938 breast cancer cases and 1, 394 matched control subjects), we analyzed the relationships of prediagnostic serum IGF‐I levels with the risk of estrogen and progesterone receptor‐positive and ‐negative breast tumors. IGF‐I levels were positively associated with the risk of ER+ breast tumors overall (pre‐ and postmenopausal women combined, odds ratio (OR)Q4‐Q1 = 1.41 [95% confidence interval (CI) 1.01–1.98] for the highest vs. lowest quartile; OR = 1.17 [95% CI 1.04–1.33] per 1‐standard deviation (SD) increase in IGF‐I, ptrend = 0.01) and among women who were diagnosed with breast cancer at 50 years or older (ORQ3‐Q1 = 1.38 [95% CI 1.01–1.89]; OR = 1.19 [95% CI 1.04–1.36] per 1‐SD increase in IGF‐I, ptrend = 0.01) but not with receptor‐positive disease diagnosed at an earlier age. No statistically significant associations were observed for ER− breast tumors overall and by age at diagnosis. Tests for heterogeneity by receptor status of the tumor were not statistically significant, except for women diagnosed with breast cancer at 50 years or older (phet = 0.03 for ER+/PR+ vs. ER−/PR− disease). Our data add to a global body of evidence indicating that higher circulating IGF‐I levels may increase risk specifically of receptor‐positive, but not receptor‐negative, breast cancer diagnosed at 50 years or older.